A Note on the Optimal Tax Lives for Assets Qualifying for the Investment Tax Credit. - Osteryoung, Jerome S.; McCarty, Daniel E.; Fortin, Karen (The Accounting Review, 1980)
Abstract ABSTRACT: Two competing factors affect the selection of the optimal life for an asset for federal income tax purposes. Both the literature and common sense suggest selection of the shortest life to recover the cash flow from the depreciation tax shield as quickly as possible. The investment tax credit mechanism, however, suggests selecting the longest life. This note resolves the conflict between the opposing factors. The methodology presented ensures the selection of the optimal tax life which will provide the maximum benefit to the firm. It is shown that a firm should normally select an asset life which gives the greatest investment tax credit.